The Role of Configurational Entropy in Amorphous Systems - Kirsten A. Graeser; James E. Patterson; J. Axel Zeitler; Thomas Rades (MDPI AG, 2010)
Configurational entropy is an important parameter in amorphous systems. It is involved in the thermodynamic considerations, plays an important role in the molecular mobility calculations through its appearance in the Adam-Gibbs equation and provides information on the solubility increase of an amorphous form compared to its crystalline counterpart. This paper presents a calorimetric method which enables the scientist to quickly determine the values for the configurational entropy at any temperature and obtain the maximum of information from these measurements.